The Influence of Product Quality on Customer Satisfaction Through Loyalty - Mariyatul Qibtiyana; Hapzi Ali (Siber International Journal of Sport Education, 2023)
This study aims to analyze the effect of product quality on customer satisfaction and loyalty in the context of marketing management. Customer loyalty is a valuable asset for a company, where customer satisfaction plays an important role in creating loyalty. Good product quality can increase customer satisfaction, which in turn will encourage repeat purchases and recommendations to other potential customers. This study uses a qualitative method through a literature study that examines various sources related to marketing management, customer satisfaction, and loyalty. The results of the study indicate that there is a positive influence between product quality and customer satisfaction on customer loyalty. Thus, product quality not only affects satisfaction but also plays an important role in building sustainable customer loyalty. These findings underline the importance of companies to continue to improve product quality to ensure customer satisfaction and loyalty .